Regulating hate crimes in Malaysia: a legal study / Muhammad Ezwar Rusydan Mohd Basir … [et al.] - Mohd Basir, Muhammad Ezwar Rusydan; Musawir, Nor Izdiyani; Talkah, Nur Atiqah; Syed Nasaruddin, Sharifah Syafiqah Nadira (2012)
Much as we desire not to have hate crime, we cannot avoid it from spreading, but we can certainly minimise its occurrence. This is a research in discussing the legal approach in current law in Malaysia in dealing with hate crimes. It analyses the needs for specific hate crime legislation by providing legal insight from hate crime legislation in United States and United Kingdom. The focus of the research is on the ability and suitability of Penal Code and Sedition Act in coping with hate crimes in Malaysia. The researchers also enlighten readers with the significance of hate crime legislation as well as the complication in enforcing such law. The hate crime legislation has developed tremendously in some countries in addressing hate crimes as more severe compared to ordinary crimes. Current law in Malaysia is inadequate in imposing punishment on hate crime perpetrators since the crime itself has not been acknowledged. Thus, the law does not provide necessary protection towards the victims who are attacked based on their perceived membership in the society. The research concludes with the findings that current law in Malaysia does not recognise the existence of hate crimes. This is because it is inadequate to deal with hate crimes and does not provide proportionate punishment towards the crime. As such, the recommendations are for the enactment of an Act to establish a committee in collecting date of hate crime cases and another Act to specifically regulate offences related to hate crimes and also judges to include bias motive as aggravating factor in delivering sentences for bias crime perpetrators.